Chemical composition and anti-mosquito potential of rhizome extract and volatile oil derived from Curcuma aromatica against Aedes aegypti (Diptera: Culicidae) - Choochote W. (2014)
Crude rhizome extracts and volatile oils of Curcuma aromatica were evaluated for chemical composition and anti-mosquito potential, including larvicidal, adulticidal, and repellent activities against the Aedes aegypti mosquito. Chemical identification achieved by GC/MS analysis revealed that xanthorrhizol, 1H-3a, 7-methanoazulene and curcumene at 35.08 and 13.65%, 21.81 and 30.02%, and 13.75 and 25.71%, were the main constituents in hexane extracts and volatile oils, respectively. Volatile oil of Cu. aromatica possessed a significantly higher larvicidal activity against the 4th instar larvae of Ae. aegypti than that of hexane extracts, with LC50 values of 36.30 and 57.15 ppm, respectively. In testing for adulticidal activity, on the other hand, hexane-extracted Cu. aromatica (LC50:1.60 μg/ mg female) was found to be slightly more effective against female Ae. aegypti than volatile oil (LC50:2.86 μg/mg female). However, the repellency of these two products against Ae. aegypti adult females differed significantly. The hexane-extracted Cu. aromatica, with a median complete protection time of 1 h (range = 1-1.5 h) when applied at a concentration of 25%, appeared to have significantly higher repellency than that of distillate oil (0.5 h, range = 0-0.5 h). The different results obtained from both products of Cu. aromatica were probably due to variety in quantity and type of active ingredients as well as the biological and physiological characteristics that differed between both developmental stages of mosquitoes, larvae, and adults.